THE CORRELATION BETWEEN PARTS OF SPEECH MASTERY AND WRITING ACHIEVEMENT - Cici Wahyuni; Loli Safitri (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This research was done because there were some problems in students’ writing, especially in parts of speech mastery. The parts of speech as a basic of grammar seem to be necessary in the process of language learning. If the students understand this, the students may construct sentence easily and the students may understand the differences between the words. Relate to this condition, the researchers wanted to investigate the correlation between parts of speech mastery and writing achievement at 11th students of MAN 4 AGAM in Academic Years 2020/2021. The design of this research was correlation research. The population of this research was all students at XI Grade of MAN 4 AGAM in academic years 2020/2021 which consist of 4 classes. The sample was 39 students taken by purposive sampling technique. The instruments of this research were test and documentation for collecting writing score of the students. To analyze the data, the researchers used the SPSS version 20 for windows. In analyzing the data, the researchers used Pearson Product Moment Correlation Coefficient to search and to find the correlation between two variables. The researchers found that the coefficient of correlation between students’ mastery in parts of speech and writing achievement at the 11th students of MAN 4 AGAM was 0,376. The correlation was positive and significant. It means that Ho was rejected and Ha was accepted. Thus, there was positive correlation between students’ parts of speech mastery and writing achievement at the 11th grade students of MAN 4 AGAM.